Adolescent Tobacco Dependency: Evidence-Based Strategies to Help Adolescents Quit - Donald Chi; Christine Riedy; Jaqueline Pickrell (Association of American Medical Colleges, 2013)
Abstract Introduction This curriculum is an innovative concept-based resource that educates medical students on the epidemiology of adolescent tobacco use and multiple evidence-based tobacco cessation strategies that can be used in clinical settings. The curriculum complements existing materials on MedEdPORTAL that focus on head, neck, and oral cancer examinations. Methods A novel video case scenario highlights the real-world consequences of adolescent tobacco use. The curriculum includes six self-guided modules based on the Centers for Disease Control and Prevention's 2006 Practical Guide on Tobacco-Use Treatment: (1) epidemiology of tobacco behaviors, (2) the 5 A's model, (3) counseling-based tobacco cessation strategies, (4) pharmacotherapeutic tobacco cessation strategies, (5) strategies to implement effective tobacco cessation programs within medical office settings, and (6) strategies on how physicians can partner with dentists to provide tobacco cessation services to adolescents. To reinforce the educational objectives and measure the effectiveness of the curriculum, a 12-item precurriculum and postcurriculum test is administered to students. Results from the pre- and posttests are used to modify the curriculum as needed for future iterations. Results The video case scenario showcased in this curriculum has been used to teach first-year dental students about adolescent tobacco disparities for 3 years. Most recent pre- and posttest data indicate that the video case scenarios are more effective than similar paper case scenarios on multiple outcomes. Discussion The objectives of the curriculum are fact based. However, the pre- and postcurriculum surveys evaluate the behavioral factors associated with students' willingness and ability to provide tobacco cessation services to adolescents. We assume that changes in knowledge will ultimately drive health providers' behaviors. In the future, we hope to address this limitation by developing comprehensive educational materials aimed at educating medical students about tobacco cessation strategies.